Programma: 2-5 januari Fine Artistes; 9-12 januari Pipi-kaka; 16-19 januari Northern Blacklight Theater; 23-26 januari Matchbox Purveyors - Flaum, Mick,
Programma: 2-5 januari Fine Artistes; 9-12 januari Pipi-kaka; 16-19 januari Northern Blacklight Theater; 23-26 januari Matchbox Purveyors.